طبيعة الاستشكال في منازعة الشهر العقاري وأثرها على استقرار الحقوق العينية - سلخ محمد لمين; درويش ماجدة (جامعة غرداية, 2024)
لقد مكنّ المشرع الجزائري لصاحب المصلحة في الطعن قضائيا في الجهة القضائية المختصة من أجل فسخ أو إبطال أو نقض أو إلغاء حق من الحقوق العينية المشهرة، مع احترام الشروط العامة والخاصة لرفع مثل هذه الدعا وى، ما ينتج عنها حكم قضائي فاصل في موضوع المنازعة، كما ضمن وضع المشرع ضمانات التنفيذ حتى يتمكن لمن صدر الحكم لصالحه من حقه واقعيا ولا يبقى الحق المحكوم به حبرا على ورق. لكن قد تظهر إشكالات في تنفيذ الحكم الفاصل في منازعة الشهر العقاري، هذه الإشكالات لها طبيعة خاصة، تستمد طبيعتها من خصوصية الحكم ذاته، هذا ما يؤثر على المساس بمبادئ الشهر العيني من بينها قاعدة قوة الثبوت المطلقة ومبدأ الأثر المطهر للشهر العيني Abstract The Algerian legislator has enabled the interested party to file a judicial appeal in the competent judicial authority in order to annul, nullify, set aside or cancel a public right in real property, while respecting the general and specific conditions for filing such lawsuits, which results in a decisive judicial ruling on the subject of the dispute. The legislator included guarantees of implementation so that the person in whose favor the ruling was issued is able to obtain his rights in reality and that the right awarded does not remain a dead letter. However, problems may arise in the implementation of the decisive ruling in a real estate notarization dispute. These problems have a special nature, deriving their nature from the specificity of the ruling itself. This is what affects the infringement of the principles of the real estate notarization, including the rule of absolute evidentiary power and the principle of the purifying effect of the notary in kind.
مداخلة
Keywords: الإشكال في التنفي; الحكم القضائي; الشهر العقاري; مبدأ قوة الثبوت المطلقة; الترقيم النهائي; problem in implementation; judicial ruling; final numbering